The Sentences that Have no Parsing in Al-Bajuri’s Footnote to the Commentary by the scholar Ibn Qasim Al-Ghazi on the Text of Abu Shuja’ - Mahdi, Baan Khairallah; Ahmed, Abdel Karim Abdel (Journal of Tikrit University for Humanities, 2024)
The research deals with study and analysis of the sentences that have no parsing in Al-Bajouri’s footnote to the commentary by the scholar Ibn Qasim Al-Ghazi on the text of Abu Shuja’, taking into account what the ancient grammarians left for us of a precious heritage that was not known in the sciences of the era at that time, and what they adopted in explaining the various sentences through scientific mechanisms that achieve clarification and clarity. It cannot be mentioned its value in determining the meaning, clarifying the purpose, and leading to the formation of texts, in addition to explaining the beauty of the structures, the good wording, and its importance in the multiplicity of possible grammatical aspects in the text. This broadcast came to know the impact of the grammatical investigations of sentences, action, and adjectives. Inferring it and how was Al-Bajouri able to benefit from these investigations - the sentences cited by the scholar Ibn Qasim Al-Ghazi in the text of Abu Shuja’ and his attempt to give preference to some grammatical aspects over others due to the possible occurrence of letters and the work of more than one grammatical aspect in a way that is consistent with the intended meaning with which it was stated.